2020
DOI: 10.1093/jac/dkaa230
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic similarity demonstrated after crushing of the elbasvir/grazoprevir fixed-dose combination tablet for HCV infection

Abstract: Background Finding a suitable treatment for HCV patients with swallowing disorders is still a major challenge. In practice, direct-acting antivirals are crushed without knowledge of adequate absorption. Crushing can alter drug exposure, possibly leading to treatment failure, development of resistance or toxicity. Currently, there is no information about crushing of the fixed-dose combination tablet of elbasvir/grazoprevir; therefore, crushing of this tablet is not recommended. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, stability and pharmacokinetic data of crushed or split tablets are not readily available. Reports of DAA tablet manipulation are limited to 2 small phase 1 pharmacokinetic studies [ 12 , 13 ] and case reports ( Table 2 ) [ 14–23 ]. Pijnenburg et al [ 12 ] conducted a phase 1, single-dose trial evaluating pharmacokinetic data of elbasvir/grazoprevir in 11 healthy adult volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, stability and pharmacokinetic data of crushed or split tablets are not readily available. Reports of DAA tablet manipulation are limited to 2 small phase 1 pharmacokinetic studies [ 12 , 13 ] and case reports ( Table 2 ) [ 14–23 ]. Pijnenburg et al [ 12 ] conducted a phase 1, single-dose trial evaluating pharmacokinetic data of elbasvir/grazoprevir in 11 healthy adult volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of DAA tablet manipulation are limited to 2 small phase 1 pharmacokinetic studies [ 12 , 13 ] and case reports ( Table 2 ) [ 14–23 ]. Pijnenburg et al [ 12 ] conducted a phase 1, single-dose trial evaluating pharmacokinetic data of elbasvir/grazoprevir in 11 healthy adult volunteers. Pharmacokinetic similarities were demonstrated between crushed and suspended elbasvir/grazoprevir tablets compared with whole tablets; thus, crushed tablets can be an administration option for patients with swallowing disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral treatment regimens that are initiated early after transplantation may be started while patients are still intubated and unable to swallow pills. There is limited pharmacokinetic data on delivery of DAAs in crushed form via enteral access tube [22][23][24]. In addition, there are several drug-drug interactions to be aware of as well including immunosuppressants, amiodarone, proton pump inhibitors, azole family drugs [25][26][27].…”
Section: Challenges Of Antiviral Therapymentioning
confidence: 99%
“…Pijnenburg et al reported the pharmacokinetic parameters of crushed EBR/GZR resulting from an open-label, randomized, cross-over study. 9 Healthy adults received a single dose of the reference (whole) tablet and crushed tablet given with 250 ml of water under fasted conditions with a 14-day washout period between each dosage form. There was no significant difference in pharmacokinetic parameters of crushed versus whole EBR.…”
Section: Elbasvir/grazoprevirmentioning
confidence: 99%